Influence of olfaction in host-selection behavior of the cassava whitefly Bemisia tabaci - Mrisho, L.; Maeda, D.G.; Ortíz, Z.M.; Ghanavi, H.R.; Legg, James P.; Stensmyr, M. (Frontiers Media, 2021)
Cassava is a vital food-security crop in Sub-Saharan Africa. Cassava crops are, however, severely affected by viral diseases transmitted by members of the whitefly species complex Bemisia tabaci. We have here investigated the role of olfaction in host selection behavior of the cassava whitefly B. tabaci SSA-ESA biotype. Surprisingly, we find that the whiteflies appear to make little use of olfaction to find their favored host. The cassava whitely shows a highly reduced olfactory system, both at the morphological and molecular level. Whitefly antennae possess only 15 sensilla with possible olfactory function, and from the genome we identified just a handful of candidate chemoreceptors, including nine tuning odorant receptors, which would afford the whitefly with one of the smallest olfactomes identified from any insect to date. Behavioral experiments with host and non-host plants, as well as with identified specific volatiles from these sources, suggest that the few input channels present are primarily tuned toward the identification of unwanted features, rather than favored ones, a strategy quite unlike most other insects. The demonstrated repellence effect of specific volatile chemicals produced by certain plants unflavored by whiteflies suggests that intercropping with these plants could be a viable strategy to reduce whitefly infestations in cassava fields.